2009
DOI: 10.1521/pedi.2009.23.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Volumes of the Hippocampus and Amygdala in Patients With Borderline Personality Disorder: A Meta-Analysis

Abstract: Individuals with borderline personality disorder (BPD) often exhibit impulsive and aggressive behavior. The hippocampus and amygdala form part of the limbic system, which plays a central role in controlling such expressions of emotional reactivity. There are mixed results in the literature regarding whether patients with BPD have smaller hippocampal and amygdalar volume relative to healthy controls. To clarify the precise nature of these mixed results, we performed a meta-analysis to aggregate data on the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 13 publications
12
78
0
5
Order By: Relevance
“…In particular, exposure to chronic or severe stress increases the incidence of such disorders (de Kloet et al, 2005;Lupien et al, 2009;Wingenfeld et al, 2010), and can act as a trigger for impaired social behaviors, especially aggression (Cordero et al, 2012;Craig, 2007;Craig & Halton, 2009;Marquez et al, 2013;Mineur et al, 2003;Neumann et al, 2010;Wood et al, 2003). While brief periods of controllable stress result in mostly adaptive physiological and behavioral changes, chronic exposure to stress has been shown to have deleterious effects on several brain structures involved in regulating social behavior, including the hippocampus, prefrontal cortex and amygdala (McEwen, 2002;Nunes et al, 2009;Sandi, 1998Sandi, , 2004. A large body of evidence implicates the differential expression of CAMs, particularly NCAM, in the mediation of stress effects on brain and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, exposure to chronic or severe stress increases the incidence of such disorders (de Kloet et al, 2005;Lupien et al, 2009;Wingenfeld et al, 2010), and can act as a trigger for impaired social behaviors, especially aggression (Cordero et al, 2012;Craig, 2007;Craig & Halton, 2009;Marquez et al, 2013;Mineur et al, 2003;Neumann et al, 2010;Wood et al, 2003). While brief periods of controllable stress result in mostly adaptive physiological and behavioral changes, chronic exposure to stress has been shown to have deleterious effects on several brain structures involved in regulating social behavior, including the hippocampus, prefrontal cortex and amygdala (McEwen, 2002;Nunes et al, 2009;Sandi, 1998Sandi, , 2004. A large body of evidence implicates the differential expression of CAMs, particularly NCAM, in the mediation of stress effects on brain and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Limbic and paralimbic systems Numerous studies have reported volumetric reductions in the limbic and paralimbic systems, particularly in the amygdala and hippocampus [135]. Niedtfeld et al [136] further confirmed that the volume loss in the amygdala in patients with borderline personality disorder is independent of a comorbid posttraumatic stress disorder.…”
Section: Borderline Personality Disordermentioning
confidence: 96%
“…However, another meta-analysis found significantly smaller left amygdala volumes in adults with PTSD than in either healthy or trauma-exposed controls (Karl et al, 2006). In addition, Nunes et al (2009) in a meta-analysis of six studies demonstrated significantly reduced volumes of both right and left hippocampi and amygdalae in patients with BPD. One meta-analysis reported that amygdala volume in children with maltreatment-related PTSD did not differ from that in healthy controls (Woon and Hedges, 2008).…”
Section: Traumatic Experiences Induce Changes In Amygdala Volumementioning
confidence: 96%